Optimizing Hospital Tariffs and Resource Allocation through Unit Cost Analysis: Lessons from a Major Indonesian Public Hospital - Igusti, Nuryanggi; Amalia AP , Andi Rizki; Arman, Arman (Journal of Current Health Sciences, 2025)
This study analyzes the unit cost structure of services at the Regional General Hospital of Makassar City to support efficient resource allocation and sustainable hospital management. Employing a quantitative descriptive survey, the analysis estimates fixed, semi-variable, and variable costs for major service units using both primary and secondary financial data. Results reveal that building-related fixed costs constitute the largest share (IDR 13,847,892,310), while semi-variable and variable costs amount to IDR 140,617,360 and IDR 2,005,849,022, respectively. The total cost of services, assessed via three standard formulas, highlights the dominance of fixed assets and energy expenses. Comparative analysis and sensitivity testing indicate that improving asset management and energy efficiency are key to optimizing hospital costs. These findings provide a robust reference for rational tariff setting and evidence-based financial policies under Indonesia’s national health insurance system. Abstrak: Penelitian ini menganalisis struktur unit cost layanan di Rumah Sakit Umum Daerah Kota Makassar guna mendukung alokasi sumber daya yang efisien dan pengelolaan rumah sakit yang berkelanjutan. Melalui survei deskriptif kuantitatif, analisis dilakukan terhadap estimasi biaya tetap, semi-variabel, dan variabel pada unit layanan utama dengan menggunakan data keuangan primer dan sekunder. Hasil penelitian menunjukkan bahwa biaya tetap yang berasal dari bangunan merupakan porsi terbesar (Rp13.847.892.310), sementara biaya semi-variabel dan variabel masing-masing sebesar Rp140.617.360 dan Rp2.005.849.022. Perhitungan total biaya layanan menggunakan tiga formula standar menegaskan dominasi aset tetap dan pengeluaran energi. Analisis komparatif dan uji sensitivitas menunjukkan bahwa optimalisasi manajemen aset dan efisiensi energi menjadi kunci pengendalian biaya rumah sakit. Temuan ini memberikan referensi kuat bagi penetapan tarif yang rasional dan kebijakan keuangan berbasis bukti dalam sistem Jaminan Kesehatan Nasional Indonesia.